Strategic Storycrafting in Niche Markets as a Catalyst for Consumer Loyalty Dynamics - Syahril Hasan; Samsurijal Hasan; Darusman; Asep Supriadi (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Competition in the increasingly segmented non-timber forest product market demands strategic differentiation that emphasizes not only product quality but also narratives reflecting ecological and social values. This study aims to analyze the influence of strategic storycrafting on consumer loyalty to forestry products based on local desires and identities. The study used a qualitative-descriptive approach with a case study method in three community forestry business groups in Yogyakarta and West Java that develop essential oil products and bamboo crafts. Data were collected through in-depth interviews with nine informants, consisting of business owners, local craftsmen, and active consumers, and supported by observations of digital promotional activities and social media documentation. Data analysis was conducted thematically through reduction, categorization, and interpretation of the meaning of consumer responses to the constructed narratives. The results show that narratives emphasizing the environment, cultural heritage, and community empowerment increase consumer emotional engagement, reflected in repeat purchasing behavior and brand loyalty. Strategic storycrafting plays a role as a catalyst in building long-term relationships between producers and consumers and increasing the added value of forestry products.